Isolation and characterization of antifungal activity of endophytic Penicillium oxalicum T3.3 as biocontrol agent for anthrachnose in dragon fruit (Hylocereus sp.) - Mamat, Suhaila (2014)
Dragon fruit plant (Hylocereus sp.) is a type of edible cactus which was widely cultivated in Malaysia. Colletotrichum gloeosporioides is a common fungal pathogen that usually affects the dragon fruit production. The occurrence of fungicide resistance pathogen had triggered the researchers to find biological control strategy using endophytic fungi to overcome this problem. Therefore, the objectives of this study are to isolate and characterize endophytic fungi from dragon fruit plant (Hylocereus sp.) and to and characterize the antifungal metabolite released by selected isolate. In this work, a number of 126 endophytic fungi were isolated from dragon fruit plant using surface sterilization technique. From both screening using dual culture test and antifungal assay respectively, isolate T3.3 exhibited potential antifungal activity against C. gloeosporioides. This isolate produced an inhibition zone with the size of 12±1.0 mm in dual culture test. Antifungal assay using 10 mg/mL of crude extract of isolate T3.3 could inhibit the growth of C. gloeosporioides by 33.33±2.89%. The diffused non volatile metabolite produced by this fungus suppressed the growth of the pathogen by 97% after 7 days of incubation. On the basis of its morphological characteristic and the ITS region sequence, isolate T3.3 was identified as Penicillium oxalicum. The Biolog FF Microplate analysis also identified this fungus as P. oxalicum Currie and Thom. The endophytic P. oxalicum T3.3 produced antifungal metabolite in Richard medium with the highest antifungal activity was on day 9 (44.0±8.54%). Fraction F9B8C5 (2.6 mg/mL) which was partially purified through bioassay guided fractionation inhibited the growth of C. gloeosporioides by 32.5%. This fungus also produced cell wall degrading enzymes; β-glucanase and chitinase with the highest activity was achieved on day 3 (3.38 U/mL) and day 6 (1.19 U/mL) respectively. Scanning electron microscopy (SEM) study revealed that antifungal metabolite released from endophytic P. oxalicum T3.3 had caused irregular hyphal growth, such as shriveling of the pathogen hyphae, necrosis of the hyphal cell wall and leakage in hyphae of C. gloeosporioides. In vivo test using detached dragon fruit revealed that sunken necrotic lesions with a radius of 13.5±0.22 mm in the fruits that not treated with crude extract reduced to 1.00±0.03 mm when treated with 100 mg/mL of crude extract. The results from this study demonstrated that there are endophytic community present in the dragon fruit plant. Endophytic P. oxalicum T3.3 which exhibited antifungal activity against C. gloeosporioides could be used as alternative method for controlling anthracnose disease in dragon fruit.